Implementasi Kewajiban Pelaporan Tenaga Kerja Bagi Pelaku Usaha Toko Swalayan di Kota Pekanbaru - Ardiansah Ardiansah; Silm Oktapani (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2020)
The existence of supermarkets that have penetrated into settlements is an attraction for the people of Pekanbaru City. However, the number of supermarkets is apparently not directly proportional to the attitude of businesses in fulfilling the obligation to report the number of workers. This study aims to identify barriers and explain the solution to the implementation of the obligations of business operators to report the number of workers in each semester ordered by the Pekanbaru City Regulation on Management of People's Markets, Shopping Centers and Supermarkets. This type of empirical legal research is used in this study, wherein a study that looks at law in society. By using data collection methods by observation, questionnaire, interview and literature review. From the results of the research conducted it can be concluded that business actors do not report the number of workers due to their ignorance of the Pekanbaru City Regional Regulation on Management of People's Markets, Shopping Centers and Supermarkets. Efforts that need to be done are related institutions need to synchronize perceptions and disseminate local regulations to business actors in order to carry out their labor reporting obligations and send letters to business actors regarding the deadline for submitting reports on the number of workers in each semester.